PRACTICAL USE OF PROJECT-BASED LEARNING TECHNOLOGIES BY A SPORTS COACH - Allayorov Muzaffar Mingaliyevich (Western European Studies, 2024)
This article delves into the challenges surrounding the effective organization of the educational process across different stages of social development, emphasizing the importance of maintaining consistency and continuity. It explores the insights of seasoned thinkers and progressive educators who have dedicated attention to these issues. Specifically, the focus of the article centres on the practical implementation of project-based learning technologies within the realm of sports coaching. By examining the application of these technologies, the research aims to shed light on innovative approaches to education, offering valuable perspectives for sports coaches seeking effective and dynamic ways to engage and educate their athletes. The findings contribute to the broader discourse on educational methodologies, offering insights applicable not only to sports coaching but also to the larger field of pedagogy.
Keywords: Project; didactic; strategic; trainer